Tracing the Evolution of the Self-Brand Connection Concept in Global Marketing Research: A Bibliometric Perspective - Loso Judijanto; Gilang Pranajasakti (The Eastasouth Management and Business, 2026)
This paper examines the evolution of the self-brand connection concept in global marketing research by adopting a bibliometric approach. The current study maps the important relationships of SBC with related concepts like brand loyalty, brand love, social media, and customer engagement in order to show how SBC has taken a central position in understanding the consumer-brand relationship. Bibliometric methods like co-citation, co-authorship, and keyword analysis will be used to disclose the intellectual structures and thematic trends over time. The findings show that the SBC concept has emerged and further developed with advances in digital engagement and social media, reflecting the greater importance of online platforms in shaping consumer emotions and behaviors. This research contributes to a better theoretical and practical understanding since the study gives a comprehensive overview of SBC literature and indicates emerging areas for future research.